Control of dengue virus in the midgut of Aedes aegypti by ectopic expression of the dsRNA-binding protein Loqs2. (December 2018) - Olmo, Roenick; Ferreira, Alvaro; Izidoro-Toledo, Tatiane; Aguiar, Eric; Faria, Isaque; Souza, Kátia; Osório, Kátia; Kuhn, Lauriane; Hammann, Philippe; Andrade, Elisa; Todjro, Yaovi; Rocha, Marcele; et al.
Abstract Dengue virus (DENV) is an arbovirus transmitted to humans byAedes mosquitoes1 . In the insect vector, the small interfering RNA (siRNA) pathway is an important antiviral mechanism against DENV2–5 . However, it remains unclear when and where the siRNA pathway acts during the virus cycle. Here, we show that the siRNA pathway fails to efficiently silence DENV in the midgut ofAedes aegypti although it is essential to restrict systemic replication. Accumulation of DENV-derived siRNAs in the midgut reveals that impaired silencing results from a defect downstream of small RNA biogenesis. Notably, silencing triggered by endogenous and exogenous dsRNAs remained effective in the midgut where known components of the siRNA pathway, including the double-stranded RNA (dsRNA)-binding proteins Loquacious and r2d2, had normal expression levels. We identified anAedes -specific paralogue ofloquacious andr2d2, hereafter namedloqs2, which is not expressed in the midgut. Loqs2 interacts with Loquacious and r2d2 and is required to control systemic replication of DENV and also Zika virus. Furthermore, ectopic expression of Loqs2 in the midgut of transgenic mosquitoes is sufficient to restrict DENV replication and dissemination. Together, our data reveal a mechanism of tissue-specific regulation of the mosquito siRNA pathway controlled by Loqs2. Although essential to restrict systemic replication, the small interfering RNA pathway fails to efficiently silence dengue virus in the midgut ofAedes aegypti in the absence of ectopic expression of the double-stranded RNA-binding protein Loqs2.